Extranodale abdominale Lymphomerkrankungen = Extranodal abdominal lymphomas - Weber, Tim; Dietrich, Sascha; Nattenmüller, Johanna (Der Radiologe, 2018)
BackgroundExtranodal manifestations occur in up to 40% of non-Hodgkin lymphomas. The prevalence of extranodal involvement has increased.ObjectivesA comprehensive overview on lymphoma involvement in the parenchymatous abdominal organs, the gastrointestinal tract, and the peritoneal cavity under due consideration of clinical implications is given.Materials and methodsA selective literature search with analysis of dedicated original research articles and reviews was carried out. Clinical guidelines are discussed.ResultsExtranodal abdominal lymphoma involvement usually occurs secondarily in advanced disease. Sites involved most frequently are the liver and the gastrointestinal tract. Extranodal abdominal lymphoma involvement is more common in the immunocompromised patient.ConclusionImaging findings of extranodal abdominal lymphoma are variable. Lymphoma is an important differential diagnosis to be considered in unclear tumor diseases.